Transformation of religion: interdisciplinary perspectives - Danz, Christian; Deibl, Jakob Helmut (Religion and Transformation in Contemporary European Society, 2023)
This volume presents different approaches to the concept of religion. Religion in modern societies is undergoing accelerated change. Traditional religious forms are dissolving and being overlaid with or replaced by new ones. This poses particular challenges for analyses of the current religious situation, which already presuppose an understanding of religion. But it is precisely this that is disputed in academic discourse about it. Against the background of this complex situation, this volume turns to the transformations of religion. It brings together inter- and transdisciplinary approaches to religion and its definition. In this way, it takes into account the fact that the transformations of religion can only be grasped by incorporating diverse methodological approaches